Hipóteses sobre a combustão entre alunos do ensino médio : a epistemologia de Gaston Bachelard - Piai, Débora (2007)
The discovery of the Oxygen integrates one of the bulk debate found at the Chemistry history and is associated to Lavoisier theory (MAAR, 1999). Many others theory were associated to a many conception until Lavoisier proposed this theory, inclusive those were acquaintance because of the association to phlogistonists, some of them was appointed from dogmas and myth, that constituted in the obstacle that Bachelard called Epistemological Obstacle. Bachelard says the obstacle was something that impedes a individual to progress his intellect (BACHELARD, 1996). This work appointed the students ideas in the fist period E. M., about the bum process, when they observed some experiments about burn. The results were analysed confronting with the Bachelard theory. The students' answers resulted in some categories: Fist Experience, General Knowledge and Error. Fist Experience is the observation result after explanation and reflexion. General Knowledge is successive generalization. And the Error is some result that does not accord with the scientific knowledge reputed right. However, to Bachelard, the reflexion about what is news can be determinant about what is mistake and to obstacle. The error to Bachelard is considerably different to the common sense about error. Error to us is considered: innocent, unthinking and did not premeditate. The Science generally casts off the error, like the teachers do, mainly class mistakes. The results show the students could couch hypothesis about what happens in the process of combustion. However, when these students expressed spontaneous conception because represents the existence of the rational thought. The teacher is the mediator between the knowledge and the student, and he can do the students improve on the difliculties proposing situations to do the student sees the error to improve on him. This process has the potency to enable an approximation more effective of the scientific knowledge.